Harmonising CERIF and INSPIRE metadata models to support multidisciplinary data sharing. (2015) - Boldrini, Enrico; Luzi, Daniela; Nativi, Stefano; Pecoraro, Fabrizio
This paper proposes a two-way crosswalk between Common European Research Information Format (CERIF) and ISO 19115 Infrastructure for Spatial Information in Europe (INSPIRE) profile metadata models. Several strategies have been investigated, depending on the quality of semantic mapping, as well as on the characteristics of the CERIF data model. A core of corresponding metadata elements has been identified, as well as a proposal of extensions of the CERIF model to be compliant with the European directive INSPIRE. Moreover, extensions of ISO concepts have also been described to provide contextual research information in the domain of environmental research data. Finally, the crosswalk has been implemented in the GI-cat discovery broker framework. Successful use cases concerning both publication and discovery of CERIF result products using the extended framework demonstrated the possibility for CERIF information to be integrated in ISO-compliant infrastructures and for INSPIRE information to be captured in CERIF.